Cinchona‐alkaloid‐based zwitterionic chiral stationary phases as potential tools for high‐performance liquid chromatographic enantioseparation of cationic compounds of pharmaceutical relevance. Issue 14 (10th June 2021) - Tanács, Dániel; Bajtai, Attila; Berkecz, Róbert; Forró, Enikő; Fülöp, Ferenc; Lindner, Wolfgang; Péter, Antal; Ilisz, István
Abstract: Enantiomers of cationic compounds of pharmaceutical relevance, namely tetrahydro‐ß‐carboline and 1, 2, 3, 4‐tetrahydroisoquinoline analogs, were separated by high‐performance liquid chromatography. Separations were performed on Cinchona ‐alkaloid‐based zwitterionic ion exchanger type chiral stationary phases applied as cation exchangers using mixtures of methanol and acetonitrile or tetrahydrofuran as bulk solvent components containing triethylammonium acetate or ammonium acetate as organic salt additives. On the zwitterionic ZWIX(+) and ZWIX(−) columns investigated, retention and enantioseparation of the studied basic analytes were influenced by the nature and concentration of the organic components of the mobile phase. The effect of organic salt additives on the retention behavior of the studied analytes can be described by the stoichiometric displacement model related to the counterion concentration. Investigations on the structure–retention relationships were performed applying different mobile phase systems for the two types of cationic analytes. For the thermodynamic characterization, parameters such as changes in standard enthalpy (Δ(Δ H° )), entropy (Δ(Δ S° )), and free energy (Δ(Δ G° )) were calculated on the basis of van't Hoff plots derived from the ln α versus 1/ T curves. In most cases, enthalpy‐driven enantioseparations were observed, with a consistent dependence of the calculated thermodynamic parameters on the mobile phase composition. Elution sequences of the studied compounds were determined in all cases.